Explore Thailand - Weaver, Harold; Weaver, Helena ([S.l. s.n.)
Features Thailand's unique culture, divided into three segments: introduction to the country, Thai arts and craft, and Thai religion and education.
Explore Thailand (26 min.) -- Arts and craft (17 min.) -- Religion and education (30 min.)
VHS.
Produced for the Tourist Organization of Thailand by Harold Weaver Productions.
Patrick Allen, commentator.
Keywords: Arts, Thai; Handicrafts -- Thailand; Education -- Thailand; Thailand -- Social life and customs; Thailand -- Religion